Effects of supervised exercise compared to non-supervised exercise early after total hip replacement on patient-reported function, pain, health-related quality of life and performance-based function – a systematic review and meta-analysis of randomized controlled trials. (January 2019) - Hansen, Sebrina; Aaboe, Jens; Mechlenburg, Inger; Overgaard, Søren; Mikkelsen, Lone Ramer
Background: The rehabilitation after a total hip replacement varies in degree of supervision; however, it remains unknown whether supervised programmes are more effective than non-supervised. Objective: This study compared the effectiveness of supervised exercise compared to non-supervised home-based exercise after total hip replacement on patient-reported function, hip-pain, health-related quality of life and performance-based function. Methods: A systematic review and meta-analysis of randomized controlled trials investigating the effect of supervised exercise compared to non-supervised home-based exercise. An electronic search was performed in Medline, Embase and CINAHL on 14 March 2018. The methodological quality was assessed using the Cochrane Risk of Bias tool. Results: Seven studies were included with a total of 389 participants. A small and non-significant difference in favour of the supervised groups was found in patient-reported function (standardized mean difference (SMD) −0.22 (95% confidence interval (CI) −0.46 to 0.02)), hip-related pain (SMD −0.03 (95% CI −0.27 to 0.21)), health-related quality of life (mean difference (MD) −3.08 (95% CI −6.29 to 0.14)) and performance-based function (SMD −0.26 (95% CI −0.68 to 0.17)) at end of treatment and in patient-reported function (MD −1.31 (95% CI −3.79 to 1.16)) at the 6- to 12-month follow-up. Limitations: The literature search was systematic, but limited to three databases. The overall quality of evidence was downgraded to moderate due to lack of blinding in included studies. Conclusion: Supervised exercise was not significantly effective compared to non-supervised home-based exercise on patient-reported function, pain, health-related quality of life and performance-based function after primary total hip replacement. Others: PROSPERO registration number: CRD42017055604.